\(-2x^2+13x-23=0\)
\(2x^2-13x+23=0\)
\(x^2-\frac{13}{2}x+\frac{23}{2}=0\)
\(x^2-2.\frac{13}{4}x+\frac{169}{16}-\frac{169}{16}+\frac{23}{2}=0\)
\(\left(x-\frac{13}{4}\right)^2+\frac{15}{16}=0\)
\(\Rightarrow x\in\varnothing\)
\(-2x^2+13x-23=0\)
\(2x^2-13x+23=0\)
\(x^2-\frac{13}{2}x+\frac{23}{2}=0\)
\(x^2-2.\frac{13}{4}x+\frac{169}{16}-\frac{169}{16}+\frac{23}{2}=0\)
\(\left(x-\frac{13}{4}\right)^2+\frac{15}{16}=0\)
\(\Rightarrow x\in\varnothing\)
phân tích đa thức thành nhân tử:
2x^3-5x^2+13x+30
Phân tích đa thức thành nhân tử: 2x^4+5x^3+13x^2+25x+15
phân tích đa thức thành nhân tử:
\(^{2x^4-7x^3-2x^2+13x+6}\)
phân tích đa thức thành nhân tử
\(3x^2-13x+36\)
Phân tích đa thức thành nhân tử:
13x^2-27x+14
phân tích đa thức thành nhân tử
7x^2-13x+6
Phân tích đa thức thành nhân tử : 6x^2 -13x + 6
Phân tích đa thức thành nhân tử dạng đoán nghiệm
a,-3x^4+20x^3-35x^2-10x+48
b,-2x^4-7x^3-x^2+7x+3
x^5-5x^4-2x^3+17x^2-13x+2
phân tích đa thức thành nhân tử:
x^3+13x^2+7x-5